Problematika Psikolinguistik dalam Pemerolehan Kosakata Bahasa Arab di Madrasah Ibtidaiyah - Ibni Trisal Adam; Amiroh Amiroh; Chandra Maulana (STIQ Amuntai, 2026)
Vocabulary is the main foundation in mastering the Arabic language, but in practice, Madrasah Ibtidaiyah (MI) students are often hindered by both linguistic and psychological issues. This research aims to describe the psycholinguistic barriers in mastering Arabic vocabulary among fifth-grade students at MI Islamiyah 02 Lebaksiu Kidul, Lebaksiu District, Tegal Regency, along with the underlying factors and the steps taken by teachers to address them. This research is of a descriptive qualitative nature based on a case study. Data sources were obtained from observations of three learning sessions, semi-structured interviews with one Arabic teacher and six selected students, vocabulary diagnostic tests on 24 students, and the review of learning documents. The data were subsequently processed through data condensation, data presentation, and conclusion drawing, with validity strengthened through source and technique triangulation. The research results show that the obstacles to vocabulary mastery stem from four interrelated aspects: (1) linguistic obstacles, including difficulties in pronouncing the phonemes خ، ع، ق، ض, spelling errors, and grammatical gender confusion; (2) cognitive obstacles, reflected in the gap between meaning comprehension scores (70.0%) and vocabulary usage in sentences (51.2%); (3) psychological factors such as fear of making mistakes and speaking anxiety; and (4) pedagogical factors, namely memorization methods that do not encourage participation compared to the use of visual media and group games. This research recommends contextual, multisensory, and socially interactive vocabulary learning as a strategy to reduce affective barriers while simultaneously strengthening students' vocabulary retention.